(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
The article continues the study of students’ interoceptive awareness. The Multidimensional Assessment of Interoceptive Awareness is a questionnaire used by leading experts to study the interoceptive awareness of people of different age groups. We used the latest version of MAIA-2, released in 2018. The original questionnaire contains 8 scales with relevant questions. In the previous article, the data of the "Noticing" scale were published. This article examines the next, fourth domain, Attention Regulation, namely the ability to maintain and control attention to bodily sensations. 7 questions (Q #16 - Q #22) with answer options on a scale from zero to five were submitted to the attention of students. 50 first-year students of the Faculty of Health, Physical Education and Sports participated in the survey. The sample was homogeneous in terms of age. The survey was conducted according to the Ukrainian version of the Multidimensional Assessment of Interoceptive Awareness (MAIA-2ukr). The following methods were used in the work: analysis of scientific and methodological literature and Internet sources, sociological method (survey MAIA-2ukr, fourth domain "4. Attention Regulation,") methods of mathematical statistics. The MS Excel program was used for statistical processing of the results. The level of interoceptive awareness of first-year students was determined using the adapted Ukrainian version of the Multidimensional Assessment of Interoceptive Awareness questionnaire (MAIA-2ukr, https://www.researchgate.net/publication/371450735_MAIA-2_UKR_Original_20220824pdf ). The purpose of the study is to assess the Attention Regulation (the ability to maintain and control attention to bodily sensations) of first-year students of the Faculty of Health, Physical Education and Sports. The results. A very important aspect of interoceptive awareness is considered in the domain "Attention Regulation" - this is attention. The ability to regulate one’s attention arises in early childhood and develops throughout a person’s life. The perception, thinking and feeling of stimuli of the external and internal environment of a person depends on this mental function of the brain. Attention ensures a quality life full of consciousness. Analysis and clear awareness of one’s actions in students leads to improvement of the general process of physical education, pedagogical control, improvement of the level of health and work capacity. In the following works, we plan to publish the results of the study of the following 4 domains of interoceptive awareness.